Importance of communities in neglected tropical disease programmes - Krentel, Alison (Henry Stewart Talks, 2019)
Mass drug administration as a means to eliminate NTDs, Defining community within the context of MDA programmes, Roles of community in NTD programme, Planning and promotion of MDA, Supervision and support during MDA, Assistance with morbidity and disability prevention